DARTS: an open-source Python pipeline for Ca2+ microdomain analysis in live cell imaging data - Woelk, Lena-Marie; Kovacevic, Dejan; Husseini, Hümeyra; Förster, Fritz; Gerlach, Fynn; Möckl, Franziska; Altfeld, Marcus; Guse, Andreas H.; Diercks, Björn-Philipp; Werner, René (Frontiers in Immunology, 2024)
Technology & Code articles present new technology, code and/or software or a new application of a known technology or software. […] can also feature studies that implement existing algorithms under novel settings.Technology & Code articles are peer-reviewed, have a maximum word count of 12,000 and may contain no more than 15 Figures/Tables. Technology & Code articles related to innovative software solutions and/or design should be novel, presented in a well-documented, human-readable format and should be placed online in a repository, with an associated DOI/URI for retrieval. To better support the code documentation, authors can also upload a metadata file in different formats (i.e. JSON-LD, Microdata, RDFa) that incorporates all the relevant information.Format: 1) Abstract, 2) Introduction, 3) Method (including any code description), 4) Results (including examples of use and limitations), 5) Discussion (including scalability and limitations).The following information must also be included: project link (e.g. sourceforge, github), operating system (e.g. Windows, Linux, platform independent), programming language (e.g. Python), any restrictions for non-academic use (e.g. licence needed).